Death‐feigning propensity varies within dice snake populations but not with sex or colour morph. (7th April 2021) - Golubović, A.; Anđelković, M.; Tomović, L.; Arsovski, D.; Gvozdenović, S.; Šukalo, G.; Ajtić, R.; Bonnet, X.
Abstract: Once cornered by a predator, prey can try to intimidate the assailant or repel it, with irritating sprays for example. If seized, they may scratch, bite or struggle to cause the predator to release its grip. At the other extreme, they can adopt passive behaviours such as death feigning (DF, i.e. thanatosis). DF is observed widely across the animal kingdom; it usually involves a combination of displays such as immobility, supination, leg‐folding, mouth opening and release of nauseating secretions. When displaying DF, individuals are highly vulnerable and effectively bet on the attitude of the predator; this risky choice is presumably under positive selection. We explored how propensity for DF varies among and within populations of dice snakes ( Natrix tessellata ). We also considered the influence of sex, body size, reproductive status, colour morph and presence of injuries ( N  = 2760 snakes; five populations). DF propensity differed among populations, possibly due to variation in local predation pressures. Larger snakes displayed DF more frequently and carried more signs of probable past predation attempts (scars and recent injuries). We found no sex effect on antipredator behaviour. Gravid females used DF less frequently compared with non‐gravid females. Differential expression of DF across populations, body sizes and reproductive status suggests that this complex behaviour was selected to respond to environmental and intrinsic factors. Future studies should explore which elements affect duration, intensity and success of DF in defence against various predators. Abstract : Once cornered by a predator, prey can adopt passive behaviours such as death feigning (DF, i.e. thanatosis). When displaying DF, individuals are highly vulnerable and effectively bet on the attitude of the predator; this risky choice is presumably under positive selection. We explored how propensity for DF varies among and within populations of dice snakes ( Natrix tessellata ). We also considered the influence of sex, body size, reproductive status, colour morph and presence of injuries ( N  = 2760 snakes; five populations). DF propensity differed among populations, possibly due to variation in local predation pressures. Larger snakes displayed DF more frequently and carried more signs of probable past predation attempts (scars and recent injuries). We found no sex effect on antipredator behaviour, but gravid females used DF less frequently compared with non‐gravid females. Differential expression of DF across populations, body sizes and reproductive status suggests that this complex behaviour was selected to respond to environmental and intrinsic factors.